<span> ϕ = (1+√5)/2 ≈ 1.618
10.4 * ϕ ≈ 16.8
10.4 / ϕ ≈ 6.4
Answer: b </span>
Answer:
f(x)=x3−x2−6x2+16x−10
Step-by-step explanation:
If 3−i is a zero, then 3+i
must be a zero as they are conjugates:
f( x ) = ( x − 1 ) ( x − ( 3 − i )) ( x − ( 3 + i )) f ( x ) = ( x − 1 ) ( x2 − x ( 3 + i ) − x ( 3 − i ) + 9 + 1 ) f ( x )) ( x − 1 ) ( x2 − 6x + 10 ) f ( x ) = x3 − x 2 − 6 x 2 + 16x − 10
Answer:
C
Step-by-step explanation:
most of the dots are along the line C
Answer:
Step-by-step explanation:
12 pages I think
Snemsjsjsjjsuduwjrbebsjenwnwnwnnnnnnjjjnnjnbbjjokbbkjvgjjbnnnnkkkkkkkkkkkk